Description and biological notes of the larva of Cionus olivieri Rosenschoeld, 1838 (Coleoptera, Curculionidae), with a comparison with other species of the tribe Cionini - Jiang, Chunyan; Caldara, Roberto; Skuhrovec, Jiri; Zhang, Runzhi (ZooKeys, 2020)
The mature larva of Cionus olivieri Rosenschoeld, 1838 is described and illustrated in detail for the first time. It is compared with those known from the same genus and other genera in the tribe Cionini and with those of the hypothesized sister tribe Mecinini in the Curculioninae. The larvae of Cionus have three distinctive diagnostic features: the reduced number of setae on the epicranium (only two or three des and one or two fs) and on the epipharyngeal lining (only two als, two ams, and no mes); i.e., distinctly fewer than the most frequent number of setae in weevils, and mandibles dentate or angulate internally near the base. If considered together with Stereonychus Suffrian, 1854, the other genus of Cionini with larvae studied in detail, it is preliminarily suggested that mature larvae of this tribe might be characterized by six main diagnostic features: (1) labial palpi one-segmented, (2) labral rods absent, (3) pedal areas swollen to form large lobes or prolegs, (4) mandible with sharp apical teeth, (5) reduced number of fs on frons, only one or two fs, and (6) reduced number of epipharyngeal setae (two or three als and two or three ams, but no mes). It was noticed that C. helleri Reitter, 1904 from Japan, a very distinct species in the genus for some characters of the adult, also possesses distinctive characters in the larva which are uncommon among known cionines. New biological data on C. olivieri with the discovery of its host plant, Verbascum songaricum (Scrophulariaceae), in central Asia are also reported.
Keywords: Curculioninae; ecology; Verbascum songaricum, weevils; immature stages; biology